Association of IL-18 promoter gene polymorphisms with rheumatoid arthritis: a meta-analysis - Li-Ping Cai; Li-Juan Zhou; Shun-Yu Lu; Ying-E Liang; Xiao-Ying Chen; Lin Liu; Jun Lin (Molecular Biology Reports, 2014)

Transcriptome profiling of CTLs regulated by rapamycin using RNA-Seq - Elliot Mattson; Lingyang Xu; Lei Li; George E. Liu; Zhengguo Xiao (Immunogenetics, 2014)

Gene-based SNP discovery and genetic mapping in pea - Anoop Sindhu; Larissa Ramsay; Lacey-Anne Sanderson; Robert Stonehouse; Rong Li; Janet Condie; Arun S. K. Shunmugam; Yong Liu; Ambuj B. Jha; Marwan Diapari; Judith Burstin; Gregoire Aubert; et al. (Theoretical and Applied Genetics, 2014)

Eutrophication as a driver of r ‐selection traits in a freshwater fish - M. Lin; M. Chevalier; S. Lek; L. Zhang; R. E. Gozlan; J. Liu; T. Zhang; S. Ye; W. Li; Z. Li (Journal of Fish Biology, 2014)
This study tested whether eutrophication could influence life‐history traits of a cyprinid, Chanodichthys erythropterus , in 10 Chinese lakes. Using the von Bertalanffy growth model, the asymptotic length ( L ∞ ) and the growth performance index ( I GRO ) were significantly affected by eutrophication. The gonado‐somatic index ( I G ) and relative fecundity ( F R ) were significantly lower in mesotrophic lakes than in eutrophic and hypertrophic lakes. These results indicate that increasing eutrophication affects the life‐history tactics of a freshwater fish.

Benthic Exchange of C, N, and P Along the Estuarine Ecotone of Lower Taylor Slough, Florida (USA): Effect of Seasonal Flows and Phosphorus Availability - Kung Jen Liu; Hsiu Ping Li; Stephen E. Davis (Wetlands, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Isolation and characterization of a mycorrhiza helper bacterium from rhizosphere soils of poplar stands - Liu Zhao; Xiao-Qin Wu; Jian-Ren Ye; Hao Li; Gui-E Li (Biology and Fertility of Soils, 2014)

Ecological suitability assessment and introduction experiment on Rosa damascena trigintipetala in Sichuan Province, China - Xiao-lan Wang; Chun-jiang Su; Li Peng; Hai-e Wang; Hai-ming Wang; Wei Liu; Ping Li; Yan Fang (Journal of Mountain Science, 2014)

Rapid growth increases intrinsic predation risk in genetically modified Cyprinus carpio : implications for environmental risk - L. Zhang; R. E. Gozlan; Z. Li; J. Liu; T. Zhang; W. Hu; Z. Zhu (Journal of Fish Biology, 2014)
The intrinsic effect of feeding regime on survival and predation‐induced mortality was experimentally tested in genetically modified ( GM ) Cyprinus carpio and wild specimens. The results clearly indicate a knock‐on effect of the GH gene ( gcGH ) introduction into the C. carpio genome on their vulnerability to predation. The experiments unequivocally showed that it is the genetic nature of the C. carpio rather than its size that affects the risk of predation. In addition, fed C. carpio were more susceptible to predation risk. Thus, the study characterizes the existence of a trade‐off between somatic growth and predator avoidance performance. Current research in Europe suggests that high uncertainty surrounding the potential environmental effects of escapee transgenic fishes into the wild is largely due to uncertainty in how the modified gene will be expressed. Understanding variables such as the cost of rapid growth on antipredator success would prove to be pivotal in setting up sound risk assessments for GM fishes and in fully assessing the environmental risk associated with GM fish escapees.

Identifying Explicit Formulation of Operating Rules for Multi-Reservoir Systems Using Genetic Programming - Liping Li; Pan Liu; David E. Rheinheimer; Chao Deng; Yanlai Zhou (Water Resources Management, 2014)

Peginterferon plus Chinese herbal therapy is associated with a higher virological response than only peginterferon therapy in chronic hepatitis C - D. Cheng; E. Liu; Y. Li; R. Liu; L. Bai; Y. Chen; Y. Wang; Y. Chu; M. Wu; G. Cheng; S. Zhao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Genome-wide association study and meta-analysis of intraocular pressure - A. Bilge Ozel; Sayoko E. Moroi; David M. Reed; Melisa Nika; Caroline M. Schmidt; Sara Akbari; Kathleen Scott; Frank Rozsa; Hemant Pawar; David C. Musch; Paul R. Lichter; Doug Gaasterland; et al. (Human Genetics, 2014)